Power Over Architecture: A Case Study on Malay Sultanate Palaces in West Kalimantan During Colonial Period (1800-1949 AD) - Uray Fery Andi; Irwin Irwin; Zairin Zain; Valentinus Pebriano; Andi Andi (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2023)
The notion of power, characterized by its ability to wield influence over others as guided by its holder’s intention, is intertwined with a spectrum of social control mechanisms encompassing force, coercion, manipulation, seduction, and authority. Malay sultanate palaces in West Kalimantan were a form of architecture hinggil (high) culture. The historical development of Malay ethnics in West Kalimantan is linked to power dynamics. This study investigates the historical development of Malay Sultanate palaces’ spatial configurations and architectural designs. It focuses on the colonial era, during which power dynamics exerted significant influence. This paper aims to ascertain the extent to which power dynamics have shaped the architectural aspects of the Malay Sultanate palaces. The analysis highlights the architectural objects and employs a historical methodology with diachronic and synchronic analyses to discern the patterns of power prevalent throughout the Sultanate’s history. Power is palpably demonstrated in effecting substantial transformations in the intent and function of the sultanate palaces, often through manipulation, seduction, and assertion of authority. These power dynamics are exemplified through architectural modifications, i.e., the controleur strategic placement and fort within the Sultanate’s vicinity, interior space reconfigurations, alterations in functionality, and symbolic embellishments reflecting the Sultanate’s authority. The colonial administration from the Dutch regime embarked on fortifying its dominion through modifications to the functional underpinnings of the palace chambers. The Dutch authority’s influence facilitated the consolidation and validation of their control. These mechanisms engendered compliance and acquiescence to the dominion of the ruling party through latent means.